Hidden Unemployement by Age and Sex in Canada : 1957-1970 - Ruggeri, Giuseppe C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
This study presents yearly estimates of hidden unemployment and job requirements for full employment in Canada by age and sex for the period 1957 to 1970. The method employed in deriving these estimates involved the calculation of the potential labour force, total and by specific age-sex groups, and the formulation of a relationship relating group employment to total employment.